THE EFFECT OF CASH TURNOVER, SALES GROWTH AND LEVERAGE ON PROFITABILITY - Reni Febrianti; Hasan Basri (Jurnal Ekonomi, 2022)
Much research has been done on profitability and the factors that influence it. Based on a review of previous research on the effect of variable Cash Turnover, Sales Growth, and Leverage on Profitability, shows different results in other words not yet consistent. Thus researchers are interested in re-testing the Cash Turnover, Sales Growth, and Leverage and their effect on profitability. This study aims to analyze the influence of Cash Turnover, Sales Growth, and Leverage on the Profitability of Manufacturing Companies in the Retail Trade sub Sector Listed on the Indonesia Stock Exchange in 2016 – 2020. The sample used 40 samples were calculated based on predetermined criteria. The data collection method uses purposive sampling. The research method uses quantitative methods, the research instrument is financial statements. This study proves that Cash Turnover, Sales Growth, and Leverage simultaneously have a significant effect on profitability. While partial cash turnover and sales growth do not affect profitability.